Estrategias didácticas activas y reformas educativas - Rodríguez Diéguez, José Luis (Revista Española de Pedagogía, 2016)
he author studies the movement of the active school in Spain. He analyzes its importance in all the educational reforms of the 20th century. The active strategies are a topic of great significance in the Spanish educational reforms from 1920. These active strategies are still pursued with great interest. The conclusion is easy. The educational reforms have not been successful. They have not achieved their explicit aims.
Keywords: Revista Española de Pedagogía